Analisis Manajemen Risiko Pada UMKM Baso Aci Pandewa - Fathil Padil, Wildan (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Every business undertaken there is bound to be competition to improve the business. Small, medium businesses or commonly called SMEs are businesses that are easy to run for anyone who wants to do business. Competition will always exist in every field of life, including MSME businesses. Every business that is run will definitely have competition and challenges that must be faced. To face the competition and challenges that exist in the business world, every MSME must innovate products and services, as well as develop human resources and technology. Every business undertaken definitely contains risks. Therefore, as MSMEs, you also need to know what risk management is. Risk management is needed to anticipate or reduce the possibility of risks occurring in a business. This article aims to describe the risks faced by Baso Aci Pandewa Bandung MSMEs. The analysis method uses descriptive analysis obtained from interviews with UMKM Baso Aci Pandewa. The results of the analysis show that Baso Aci Pandewa MSMEs have risks, namely raw material risk, financial risk, marketing risk. the. Based on the SWOT analysis of Baso Aci Pandewa UMKM, its strength is that Baso Aci Pandewa is a culinary dish that is designed instantly to make it easier for customers to serve it. The weakness of this baso aci business is that the raw materials quickly go stale if there are any leftovers. The opportunity for this business is that it can be developed to a wider area. Meanwhile, the threat to the baso aci culinary business is from the same business and also culinary delights that come from sago flour as the raw material.